Three-dimensional woven structural glass fiber/polytetrafluoroethylene (PTFE) composite antenna with superb integrity and electromagnetic performance. (1st February 2022) - Zhang, Kun; Zhao, Da; Chen, Wei; Zheng, Liangang; Yao, Lan; Qiu, Yiping; Xu, Fujun
Abstract: Integration of electronic devices into composites is imperative for the development of smart structural materials, which can address the structure limitations, such as the delamination of structures and degradation of electronic performances. In this study, the 3D orthogonal woven composite antenna (3DIMA) based on glass fiber and PTFE polymer were manufactured for the first time by multiple impregnation and sintering processes to obtain adequate PTFE penetration and good mechanical properties. Consequently, the as-produced 3D integrated microstrip antenna (3DIMA) showed good mechanical properties (bending, compression, impact strength) and electromagnetic performance with proper radiation pattern as well as gain value (1.3 dB), showing similar performance with conventional microstrip antenna. Besides, the simulated return losses and radiation patterns obtained from professional antenna software agreed well with the tested results. Furthermore, the 3DIMA maintained similar radiation pattern even under the low velocity impact with the kenitic engery of 15 J, exhibiting excellent structural integrity.